Peran Brand Ambassador Twice Terhadap Minat Beli Produk Scarlett Whitening Di Banjarmasin - Lutfi Aulia; Teguh Wicaksono; Azzahraty (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to test and analyze the role of Twice's brand ambassador on the buying interest of Scarlett Whitening products in Banjarmasin. This study used quantitative methods, with data analysis using simple linear regression, t-test, and determination coefficient test. The population in the study was all students of the Faculty of Economics, Class of 2019 UNISKA. The sampling technique uses purposive sampling with a sample of 87 respondents, with a questionnaire as a research instrument. The results showed that brand ambassadors had a significant effect on the interest in buying Scarlett Whitening products in Banjarmasin. This factor is caused by the attractiveness, popularity, and trust given by consumers to brand ambassadors, where the attractiveness and popularity possessed by the brand ambassador will greatly affect consumer buying interest.